Bimbingan Baca Tulis Al-Qur'an sebagai Upaya Peningkatan Kualitas Bacaan Qur'an Siswa Baru - Damanik, Hendah Damayanti; Mubarok, Ramdanil; Rosma, Rosma (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Community service related to guidance on reading and writing the Qur'an as an effort to improve the reading of the Qur'an for new students at SMP Negeri 2 Sangatta Utara is carried out with the aim of providing guidance to new students on how to read and write the Qur'an properly. and right. The method used is participatory Action Research research method. Participatory Action Research, which is usually abbreviated as PAR, is a service research activity where the author is directly involved in a participatory manner as a mentor at the service location. The result is that with the guidance of reading and writing the Qur'an to the students of SMP Negeri 2 Sangatta Utara, they can improve the students' reading of the Qur'an. In addition, there is also an increase in the writing of the verses of the Qur'an by looking at the text. Thus enabling the convenience of the Islamic religious learning process in the classroom. The problem is that the intensity of the bombing is short so that the guidance on writing the Qur'an has not been completed without looking at the text of the verse. The guidance is only limited to recognizing letters that can be spliced ​​and cannot be spliced. This becomes input and advice for Islamic religious teachers to continue guidance in writing the Qur'an without looking at other opportunities.